Potential of a Spectroscopic Measurement Method Using Adding–Doubling to Retrieve the Bulk Optical Properties of Dense Microalgal Media. Issue 10 (October 2014) - Bellini, Sarah; Bendoula, Ryad; Latrille, Eric; Roger, Jean-Michel
In the context of algal mass cultivation, current techniques used for the characterization of algal cells require time-consuming sample preparation and a large amount of costly, standard instrumentation. As the physical and chemical properties of the algal cells strongly affect their optical properties, the optical characterization is seen as a promising method to provide an early diagnosis in the context of mass cultivation monitoring. This article explores the potential of a spectroscopic measurement method coupled with the inversion of the radiative transfer theory for the retrieval of the bulk optical properties of dense algal samples. Total transmittance and total reflectance measurements were performed over the 380-1020 nm range on dense algal samples with a double integrating sphere setup. The bulk absorption and scattering coefficients were thus extracted over the 380-1020 nm range by inverting the radiative transfer theory using inverse-adding-doubling computations. The experimental results are presented and discussed; the configuration of the optical setup remains a critical point. The absorption coefficients obtained for the four samples of this study appear not to be more informative about pigment composition than would be classical methods in analytical spectroscopy; however, there is a real added value in measuring the reduced scattering coefficient, as it appears to be strongly correlated to the size distribution of the algal cells.